PENINGKATAN PERKEMBANGAN MOTORIK HALUS ANAK MELALUI KEGIATAN FINGER PAINTING - Wena, Putu; Subawa, I Putu; Suparya, I Ketut (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
This classroom action research aims to improve the fine motoric development of children in group A TK Weda Purana Pemaron, through finger painting activities. The subjects of this classroom action research were group A children of TK Weda Purana Pemaron, totaling 5 children. This classroom action research was conducted in two cycles. Each cycle goes through the planning, implementation, observation and reflection stages. Methods of data collection are done through performance, observation, and documentation. Data analysis in this study used a qualitative descriptive analysis. Based on the results of the pre-cycle before classroom action research, it shows that the child’s fine motoric development has not yet reached optimal results, which only reached a percentage of 50% or the category began to develop. So that action is taken in the first cycle to achieve results with a percentage of 70% or developing categories as expected, while in cycle II achieve results with a percentage of 90% or very well developed categories. With these results indicate that the indicators of success have been achieved.